The Effectiviness of The Generative Learning Model with Cognitive Conflict Strategy on Students’ Science Literacy in Fluid Material in Grade XI - Siti Rahma Fitri Yani; Akmam, Akmam; Darvina, Yenni; Novitra, Fuja (Journal of Innovative Physics Teaching, 2025)
Science literacy is an important skill in modern science education, involving understanding concepts, reasoning scientifically, and applying science in everyday situations. However, the level of science literacy among students in Indonesia is still low, as seen in the 2022 PISA results, which are below the global average. This shows the need for learning models that can increase cognitive participation and form a deep conceptual understanding. Generative learning models, which focus on knowledge construction through the integration of prior knowledge with new learning experiences, are considered suitable for improving science literacy, especially when combined with cognitive conflict strategies. This study aims to examine the impact of a generative learning model that uses cognitive conflict strategies on students' science literacy on the topic of Fluids in Grade XI Phase F. This study applied a quasi-experimental method with a single group pretest-posttest design. The results show an increase in the average score from 63.75 on the pretest to 91.25 on the posttest. The hypothesis test produced a significance value of 0.000 (less than 0.05) with an N-Gain of 0.7667, which is classified as high. These findings prove that the generative learning model with cognitive conflict strategies is effective in improving students' science literacy.